2014
DOI: 10.1117/1.jbo.19.8.080901
|View full text |Cite
|
Sign up to set email alerts
|

Review of recent developments in stimulated emission depletion microscopy: applications on cell imaging

Abstract: Abstract. Stimulated emission depletion (STED) microscopy is one type of far-field optical technique demonstrated to provide subdiffraction resolution. STED microscopy utilizes a donut-shaped depletion beam to limit the probe volume to be much smaller than a diffraction-limited spot. Resolutions as small as a few tens of nanometers laterally are reported for cell analysis. The different versions of STED microscopes are described and contrasted in terms of their applicability for biological imaging. Finally, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 100 publications
0
21
0
Order By: Relevance
“…Unfortunately, the resolution limit of classical light microcopy does not allow us to distinguish individual MTs from apparent bundles. Yet, STED microscopy, which improves the spatial resolution about five times (Neupane et al, 2014), allowed us to do so to a certain extent (Fig. 2).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Unfortunately, the resolution limit of classical light microcopy does not allow us to distinguish individual MTs from apparent bundles. Yet, STED microscopy, which improves the spatial resolution about five times (Neupane et al, 2014), allowed us to do so to a certain extent (Fig. 2).…”
Section: Resultsmentioning
confidence: 94%
“…To further explore MT arrays in the eb1a-2 eb1b-3 double-mutant plants, we used stimulated emission depletion (STED) microscopy (Neupane et al, 2014) to achieve super resolution imaging on living seedlings. Previous studies showed that cortical MTs are assembled as bundles through tight lateral association (Ledbetter and Porter, 1963).…”
Section: Resultsmentioning
confidence: 99%
“…Patterned illumination techniques mainly include stimulated emission depletion microscopy (STED), saturated structured illumination microscopy, and the reversible saturable optical fluorescence transitions technique [65]. In optical physics, a point light source will form a fuzzy spot when focused on by the objective lens.…”
Section: Box 2 Super-resolution Fluorescence Imagingmentioning
confidence: 99%
“…1A), which is equivalent to making a blunt tip of a pen sharper so that it can write sharp letter. To calculate the resolution of STED microscope, the equation (1) has to be modified as (Hell and Wichmann 1994, Hell 2007, Neupane et al 2014, Neupane et al 2015:…”
Section: Introductionmentioning
confidence: 99%
“…and stained with dye] and living cells, studying functions of neuronal tissues and cells, and studying movement of biomolecules in living cells are demonstrated. The details, of which can be found in the following works ( , Stender et al 2013, Neupane et al 2014, Neupane et al 2015. Up to this point, very few research articles related to applicability of STED microscope in materials science research are published (Harke et al 2008, Lauterbach et al 2010.…”
Section: Introductionmentioning
confidence: 99%